[​4+2] versus [​2+2] Homodimerization in P(V) Derivatives of 2,4-Disubstituted Phospholes - Guillaume Bousrez; Emmanuel Nicolas; Agathe Martinez; Sylviane Chevreux; Florian Jaroschik (Heteroatom Chemistry)
Phosphole P(V) derivatives are interesting building blocks for various applications from ligand synthesis to material sciences. We herein describe the preparation and characterisation of new 2,4-disubstituted oxo-, thiooxo-, and selenooxophospholes. The nature of the substituents on the phosphole ring determines the reactivity of these compounds towards homodimerization reactions. Aryl and trimethylsilyl substituted oxophospholes undergo selective [4+2] dimerization, whereas, for thiooxo- and selenooxophospholes, light-induced, selective [2+2] head-to-head dimerization occurs in the case of aryl substituents. DFT calculations provide some insights on these differences in reactivity.